An unknown Russian memoir by Aagvan Dorjiev - Andreev, Aleksandr Ivanovič (Inner Asia, 2001)
This article describes the literature on Aagvan Dorjiev available in various languages (Tibetan, Mongolian, Buryat, Russian and English). It brings to the attention of readers a new short memoir of Dorjiev, written in Russian and hitherto unpublished. This memoir, almost certainly written by Dorjiev himself, gives us an insight into the "Great Game" as seen from someone working within it on the Russian side. Supplying an English translation of the memoir as an appendix, the article discusses the new information it provides. (Inner Asia/DÜI)